2021
DOI: 10.1186/s12882-021-02514-8
|View full text |Cite
|
Sign up to set email alerts
|

Practices and pitfalls in medication adherence in hemodialysis settings – a focus-group study of health care professionals

Abstract: Background Medication nonadherence is common among patients with hemodialysis, leading to poorer patient outcomes. Health care professionals have an important role in assessing risk of nonadherence and intervening to support adherence. The aim of this study was to explore physicians’ and nurses’ current medication adherence practices in hemodialysis settings. Method A generic qualitative design with inductive content analysis and focus group method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…37 Because of their chronic renal disease and complex medication regimens, patients on dialysis can also experience cognitive impairment that may affect the clinician’s ability to comprehensively perform medication reconciliation given already limited time constraints. 21 Patients may also lack sufficient resources to learn about the medications they are taking, including their potential harms. The therapeutic relationship between the patient and the clinician can also influence initiation of a deprescribing trial or affect readiness to attempt a drug deprescription.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…37 Because of their chronic renal disease and complex medication regimens, patients on dialysis can also experience cognitive impairment that may affect the clinician’s ability to comprehensively perform medication reconciliation given already limited time constraints. 21 Patients may also lack sufficient resources to learn about the medications they are taking, including their potential harms. The therapeutic relationship between the patient and the clinician can also influence initiation of a deprescribing trial or affect readiness to attempt a drug deprescription.…”
Section: Discussionmentioning
confidence: 99%
“…Guidelines for deprescribing contain long lists of rules that preclude memorization; some may contain conflicting recommendations for patients taking 10 to 15 medications; and not all guidelines explain how to deprescribe (eg, when and how to taper and what rebound symptoms to watch out for). 2,[21][22][23] We therefore integrated the dialysis-specific deprescribing recommendations into the MedSafer ruleset, coupled them with links to patient deprescribing empowerment brochures, and added instructions for tapering where required.…”
Section: Background and Rationalementioning
confidence: 99%
“…Due to the complexity of individual regimens, which require the administration of various doses, forms, and frequency, maintaining continuous adherence is a major challenge among HD patient. 4 Studies shown that an average prevalence rate of 52.5% medication non-adherence was reported among HD patients. 5 This shows medication adherence among ESRD patients remains a challenge.…”
mentioning
confidence: 99%